Gastric Antral Vascular Ectasia (GAVE) a case report, review of the literature and update of techniques. (September 2022) - Fortuna, L.; Bottari, A.; Bisogni, D.; Coratti, F.; Giudici, F.; Orlandini, B.; Dragoni, G.; Cianchi, F.; Staderini, F.
Abstract: Introduction and importance: Gastric Antral Vascular Ectasia is a rare disorder that causes up to 4 % of severe acute gastrointestinal bleeding. It affects elderly females with iron deficiency anemia due to chronic blood loss as a common presenting sign. Case presentation: We report the case of a 70-year-old man admitted to the Urgency Department for severe asthenia associated with abdominal pain and severe anemia. An urgent upper endoscopic examination showed antral hyperemic streaks and vascular ectasias extending from the pyloric ring to the gastric body as well as signs of recent bleeding. Histological results demonstrated the pathognomonic features of GAVE. Clinical discussion: The first line treatment is considered argon plasma coagulation (APC), given its wider availability, safety, efficacy and cost-effectiveness. In current literature, other therapies and different types of endoscopic treatments have been proposed, such as EBL, RFA and Yag: laser. To date, there is no specific recommendation that privileges one method over another in the treatment of GAVE, although APC has proven effective and even better in terms of complications and costs than the other techniques. Conclusion: In our experience, endoscopic coagulation with APC probes is a relatively easy-to-use technique with low cost, minimal invasiveness and provides immediate results. On the other hand, a standardized algorithm is also required concerning to the different subtypes to give the best treatment in every case. Highlights: Gastric Antral Vascular Ectasia is a rare disorder that causes up to 4% of severe acute gastro-intestinal bleeding. A 70-year-old man was admitted to the Urgency Department for abdominal pain and severe anemia. The urgent upper endoscopic examination and the histological results demonstrated the pathognomonic features of GAVE. APC probes is a relatively easy-to-use technique with low cost, minimal invasiveness and provides immediate results. A standardized algorithm is also required in relation to the different subtypes in order to give the best treatment in every case.